Opportunistic pathogens and polycocktail drugs fuel dynamic public health threats during the opioid crisis - John H. Boman; Nara Souza; Jasmine Light; Dawson Holt; Shannon Jones; Angelic King; Mahjida Berryman; Sarah A. Shuda; Mia Borrelli; Barry K. Logan; Amanda L. A. Mohr; Hans Wildschutte (PLoS ONE, 2025)
More than 100,000 preventable deaths have occurred each year in the United States since 2021 from intravenous drug use. A challenging problem for clinicians, researchers, and public health workers involves understanding a dynamic opioid crisis for implementing state and national policy to support the rehabilitation and treatment of individuals who inject drugs. To address these issues, this study used drug needles obtained from people who inject drugs to address three goals: First, based on a forensic analysis, what narcotics are contained in the needles? Second, are there non-viral pathogens contained in the needles? Third, if pathogens are identified, can potential infections be treated with common medication? Results demonstrate that 27 total psychoactive substances (most listed in the Drug Enforcement Administration’s schedule of controlled substances) were present in 50 randomly selected syringes. The average used drug needle contained eight psychoactive substances. In addition to drugs, non-viral culturable microbes in used syringes were identified. The most problematic of these was an opportunistic fungal pathogen, Candida parapsilosis, that persists on skin and for which few medical options exist for treatment. To thus facilitate antifungal discovery, soil-derived bacteria that inhibit the growth of Candida pathogens were identified. Transposon mutagenesis was utilized to discover the biosynthetic gene cluster involved in antifungal activity which encoded a non-ribosomal peptide synthetase. Although limited to syringes from only one mid-western city, results suggest that potentially fatal, emergent, and opportunistic pathogens may have the ability to persist in used drug syringes. While this finding may be alarming to public health and public safety officials, the identification of bacteria which inhibits the growth of Candida parapsilosis poses a foundation for antifungal drug discovery.